The Effect of Pindstrup Growing Media on the Growth and Yield of Melon Plants (Cucumis melo L.): Pengaruh Media Tanam Pindstrup terhadap Pertumbuhan dan Hasil Tanaman Melon (Cucumis melo L.) - Saputra, Aditya Fajar; Abror, M. (Procedia of Engineering and Life Science, 2025)
This study aims to determine the effect of Pindstrup growing media on the growth and yield of melon plants (Cucumis melo L.) in Netafarm, Taman Sidoarjo. The research was conducted using two different planting media: Pindstrup peat moss and conventional soil media as control. Growth parameters observed include plant height, leaf number, fruit weight, and fruit quality. The results showed that Pindstrup media significantly affected melon growth, resulting in better plant vigor, higher fruit weight, and improved fruit sweetness compared to the control. Therefore, Pindstrup media can be recommended as an effective growing medium for melon cultivation in controlled farming systems.